EXPLORING THE INFORMING ASPECTS OF SCIENCE TEACHERS’ ADOPTION OF DIGITAL TECHNOLOGY IN TEACHING SCIENCE IN MANZINI PRIMARY SCHOOLS OF ESWATINI (NAU Journal of Technology and Vocational Education, 2026)
The adoption of digital technology into science education has become a global priority. This study explores the informing aspects of science teachers’ adoption of digital technologies in teaching Science curriculum in Eswatini. The objective of this study was to determine the informing aspects of science teachers’ adoption of digital technology in teaching Science curriculum in primary schools. The study was guided by the Unified theory of acceptance and use of technology (UTAUT). The study adopted an interpretivist research paradigm using the qualitative research approach where a multiple case study research design was utilised. Convenience sampling was used to select three primary schools and purposive sampling was used to select six (6) participants. The data was generated using two instruments: semi-structured interviews and document analysis. Furthermore, the study adopted a thematic as means of organising data for analysis. The findings of the study revealed that the Science were informed by personal, school and external factors to adopt digital technologies in their teaching practices. Based on the findings of the study, the researchers recommended that a peer mentoring program in the school’s clusters so that teachers who are proficient with technology can assist others and that schools should ensure that physical infrastructure and resources are available for the teachers and learners to effectively adopt digital technology in the teaching and learning process.
Keywords: Adoption; Informing; Digital technology; Science